The Influence of Social Media Marketing on Instagram on the Decision to Purchase Thrift Fashion Products (Study of Followers of the Instagram Account @Sechondshop.co) - Agnesia Sulastri Aru; Moch. Nurhidayat; Fitria Setyaningrum (International Research & Development for Human Beings (IRDH), 2026)
This study aims to analyze the influence of social media marketing on Instagram on thrift fashion product purchasing decisions among followers of the account @Sechondshop.co. The study used a quantitative approach with an explanatory method. The study population was active followers of the account @Sechondshop.co, using a non-probability sampling technique. Data were collected through a questionnaire and analyzed using simple linear regression. The results of the study indicate that social media marketing has a positive and significant influence on purchasing decisions, as evidenced by a t-test with a calculated t-value greater than the t-table. The coefficient of determination (R²) of 0.755 indicates that social media marketing influences purchasing decisions by 75.5%, while the remainder is influenced by other factors outside the study. This finding confirms that social media marketing through Instagram plays a significant role in driving purchasing decisions for thrift fashion products among followers of the @Sechondshop.co account.